PENGEMBANGAN DESA DIGITAL DALAM PELAYANAN PUBLIK DAN KEARSIPAN BERBASIS TEKNOLOGI INFORMASI DI GAMPONG REULET TIMUR - Fakhrurrazi Fakhrurrazi; Mutammimul Ula; Ade Luky Setiawan; Asma Mauli Arpika; Nurhafni Nurhafni (LPPM Universitas Al Muslim, 2022)
The development of digital-based smart villages in Indonesia can increase economic activity and productivity in rural areas. The implementation of digital village innovations is able to improve public services by utilizing technology, thus creating effectiveness and efficiency in providing services. However, not all villages can keep up with rapid technology developments. To overcome these problems, it is necessary to provide information technology infrastructure for villages. Currently, the government by using the village fund instrument has started to provide technological facilities and infrastructure to the village government. However, the existence of this equipment had not run optimally as a result of lack of knowledge and skills in information and technology, especially in the field of public services and archives. This service aimed to make village apparatus and residents familiar with technology and make filing easier for village officials. Furthermore, for the development of digital villages there will be training in introducing technology to residents. The results of this service facilitated village officials in administration and providing detailed information about village activities, assisting partners in accelerating services and disseminating information related to villages in all fields, especially in the administrative field.